FINANCIAL LITERACY, SOCIAL INFLUENCE AND THE USE OF DIGITAL PAYMENTS: A LITERATURE REVIEW - Oktafian Histori S. (Universitas Kristen Indonesia Toraja, 2022)
This study investigated the role of financial literacy and social influence in the actual usage of digital payment as a fintech service systems in an effort to gather information and the degree of risk that users will experience, taking into account the advantages received. This study utilized a descriptive qualitative strategy coupled with a literature review method for data collection, namely the acquisition of data from publications and journals pertaining to the usage of digital payment systems. The data analysis technique employs the approach of deriving conclusions by objectively, systematically, and generally recognizing the many specific qualities of a message. The findings indicated that financial literacy and social influence have a substantial impact on the utilization of digital payment systems. The usage of digital payment services as a type of risky financial behavior raises knowledge and comprehension of financial goods, which will affect judgments on whether or not to utilize these products. This study is limited to a literature review and paves the way for future empirical studies to analyze the elements and dimensions of financial literacy and social influence in the usage of digital payment services in more depth.